Hubungan Tingkat Pengetahuan dengan Perilaku Ibu Tentang Pencegahan Diare pada Anak di UPT Puskesmas Jekan Raya Kota Palangka Raya Tahun 2022: Relationship Level of Knowledge with Behavior Mother About Preventing Diarrhea in Children at UPT Puskesmas Jekan Raya Palangka Raya City Year 2022 - Jumesy Milianie; Mariaty A. Sangkai; Melisa Prasida (Jurnal Surya Medika (JSM), 2023)
Diarrhea is a condition in which a person defecates 3 (three) times or more in one day, the factor causing diarrhea in children is due to behavior that does not maintain cleanliness. so that viruses or bacteria that stick to the hands also enter the body through the food that is eaten. The purpose of this study was to determine the level of knowledge and behavior of mothers with the prevention of diarrhea in children at the UPT Puskesmas Jekan Raya, Palangka Raya City. The method used is Total Sampling. The design of this study used an analytical survey with a Cross Sectional approach. The research sample was 43 mothers who visited the UPT Puskesmas Jekan Raya. The research data was taken using a questionnaire after tabulating the data in univariate analysis and bivariate analysis using the Chi-squere test. The results of the study, the significance value of P-value = 0.002 < = 0.05, there is a relationship between Mother's Knowledge and Behavior and Prevention of Diarrhea in Children at UPT Puskesmas Jekan Raya. The advice given to mothers is that they can increase their knowledge through print media or social media so that they can add experience in terms of preventing diarrhea in children.